Digital Marketing Among the Millennials Generation of MSMEs in Serdang Bedagai Regency - Masril, Munzaimah; Lubis, Fatma Wardy (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
This article intends to describe the phenomenon of conventional marketing transitioning to digital marketing by millennial-generation MSMEs in Serdang Bedagai Regency in marketing their products. Internet access in Indonesia is generally quite extensive; at this time, the average house has one cellphone that has an Internet connection. The millennial generation of MSME actors in Serdang Bedagai Regency has also known the benefits and advantages of digital marketing. However, the marketing method and the choice of digital platforms cannot be generalized for all types of MSMEs and their target markets. This article is based on qualitative research and descriptive analysis. The results found that most digital marketing was carried out through applications on smartphones rather than computers (laptops or desktops). The choice of media platforms is also adjusted to the target market and economic level as well as the user's understanding, so many MSME actors prefer social media based on mobile applications that are easy for them to access.